Państwowa Inspekcja Pracy jako gwarant prawidłowego dokumentowania pracy w szczególnych warunkach lub o szczególnym charakterze - Jabłoński, Andrzej (Wydawnictwo Uniwersytetu Wrocławskiego, 2024)
The article presents the role of the State Labour Inspection in terms of control and supervision of the documentation of work in special conditions or of a special nature. In the current state of the law, the State Labour Inspection may carry out a substantive assessment of an employee’s working conditions. An important issue in the article is whether an order issued by the State Labour Inspection is binding on the pension authorities and the social insurance court as to whether work was performed in special conditions or of a special nature.
Keywords: special conditions; retirement; records; order; State Labour Inspection